2011
DOI: 10.1186/1475-2891-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Effect: an Italian picture

Abstract: BackgroundThe purpose of this study was to evaluate the overall diet quality effects, mainly on antioxidant nutritional status and some cytokines related to the cellular immune response as well as oxidative stress in a healthy Italian population group.MethodsAn observational study was conducted on 131 healthy free-living subjects. Dietary intake was assessed by dietary diary. Standardised procedures were used to make anthropometric measurements. On blood samples (serum, plasma and whole blood) were evaluated: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 46 publications
5
53
0
Order By: Relevance
“…Seventeen studies reported statistically significant associations with biomarkers of low‐grade chronic inflammation. Positive associations were reported between the different healthy a priori patterns and the anti‐inflammatory markers adiponectin and IL‐10 . Ten studies reported inverse associations for CRP levels and dietary indices that were almost all MDS/alternative MDS or HEI/alternative HEI .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies reported statistically significant associations with biomarkers of low‐grade chronic inflammation. Positive associations were reported between the different healthy a priori patterns and the anti‐inflammatory markers adiponectin and IL‐10 . Ten studies reported inverse associations for CRP levels and dietary indices that were almost all MDS/alternative MDS or HEI/alternative HEI .…”
Section: Resultsmentioning
confidence: 99%
“…Screening of reference lists led to the inclusion of two additional studies . In total, 46 studies were included in the present review …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean diet is associated with increased circulating plasma antioxidant levels and decreased oxidative stress (Azzini et al, 2011, Yubero-Serrano et al, 2011. The protective properties of this diet may be derived not only from its increased antioxidant concentration but also through its high raw food intake, lower production of cooking-related oxidants and consequent decreased use of nutritional and endogenous antioxidants, and increased fibre intake (Ghiselli et al, 1997).…”
Section: Diet and Its Effect On Oxidative Stressmentioning
confidence: 99%
“…For this reason, the MD dietary model is considered by the scientific community an effective model for the prevention of non-communicable diseases (Azzini et al, 2011). Moreover, it is considered a sustainable diet model that respects the environment, promotes the bio-diversity and the local cultural heritages (Burlingame & Dernini, 2011).…”
Section: Introductionmentioning
confidence: 99%